Terminal fucosylation of haptoglobin in cancer-derived exosomes during cholangiocarcinoma progression - Choi, Hyewon; Ju, Sungeun; Kang, Keunsoo; Seo, Moon-Hyeong; Kim, Jin-Man; Miyoshi, Eiji; Yeo, Min-Kyung; Park, Seung-Yeol (Frontiers in Oncology, 2023)
Background: Cholangiocarcinoma (CCA) is a silent tumor with a high motility rate due to the difficulty of early diagnosis and prediction of recurrence even after timely surgery. Serologic cancer biomarkers have been used in clinical practice, but their low specificity and sensitivity have been problematic. In this study, we aimed to identify CCA-specific glycan epitopes that can be used for diagnosis and to elucidate the mechanisms by which glycosylation is altered with tumor progression. Methods: The serum of patients with various cancers was fractioned into membrane-bound and soluble components using serial ultracentrifugation. Lectin blotting was conducted to evaluate glycosylation. Proteins having altered glycosylation were identified using proteomic analysis and further confirmed using immunoblotting analysis. We performed HPLC, gene analysis, real-time cargo tracking, and immunohistochemistry to determine the origin of CCA glycosylation and its underlying mechanisms. Extracellular vesicles (EV) were isolated from the sera of 62 patients with CCA at different clinical stages and inflammatory conditions and used for glycan analysis to assess their clinical significance. Results: The results reveal that glycosylation patterns between soluble and membrane-bound fractions differs significantly even when obtained from the same donor. Notably, glycans with α1-3/4 fucose and β1-6GlcNAc branched structures increase specifically in membrane-bound fractions of CCA. Mechanically, it is primarily due to β-haptoglobin (β-Hp) originating from CCA expressing fucosyltransferase-3/4 (FUT 3/4) and N-acetylglucosaminyltransferase-V (MGAT5). Newly synthesized β-Hp is loaded into EVs in early endosomes via a KFERQ-like motif and then secreted from CCA cells to induce tumor progression. In contrast, β-Hp expressed by hepatocytes is secreted in a soluble form that does not affect CCA progression. Moreover, evaluation of EV glycosylation in CCA patients shows that fucosylation level of EV-Hp gradually increases with tumor progression and decreases markedly when the tumors are eliminated by surgery. Conclusion: This study suggests that terminal fucosylation of Hp in cancer-derived exosomes can be a novel glycan marker for diagnosis and prognosis of CCA. These findings highlight the potential of glycan analysis in different fractions of serum for biomarker discover for other diseases. Further research is needed to understand the role of fucosylated EVs on CCA progression.